Investigation of bioflocculant as dewatering aid in sludge treatment - Jami, Mohammed Saedi; Mel, Maizirwan; Mohd Ariff, Aysha Ralliya; Abdulazeez, Qabas Marwan (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Sludge treatment is one of the most important and expensive steps in water and wastewater treatment plants. Chemical conditioners such as polyaluminium chloride, aluminium sulfate, Fenton’s reagent, gypsum, and polyacrylamide can produce by-products, which cause health and environmental problems. Moringa oleifera (MO) seeds can be used as natural alternative to chemical conditioners. The bioactive materials have to be extracted from MO seeds for good performance. Treatment methods of MO seeds investigated in this study were crude MO seeds, extraction by NaCl (1 M), and defatted MO seeds using hexane solvent. Synthetic sludge samples were prepared using kaolin suspension (5% w/v). The best extraction method was determined based on settling velocity (Vs) and sludge volume index (SVI) as indicators. Results showed that extraction by NaCl gave the best results of 0.41 cm/min of settling velocity and SVI of 63.39 mL/g. SVI value greater than 150 mL/g indicates poor settling qualities whereas the control sludge of the current study was 100 mL/g. The selected extraction method was optimized with respect to three process conditions: MO seeds concentration, mixing speed and contact time. The experiments were designed using 2 Level Factorial Design by Design-Expert software. The optimum process conditions were seed concentration of 3250 mg/L, mixing speed of 100 rpm. MO seeds can be considered a natural coagulant that can be used as main sludge conditioner.